2021
DOI: 10.1088/1755-1315/788/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Detection of growth hormone (GH|MspI,GHR|AluI, Pit1|HinfI) genes polymorphism and its association with body weight of Grati-Bali Cattle (Bos sondaicus)

Abstract: Bali cattle is the only native Indonesian cattle that still exist and well developed. Bali cattle are known to have adaptability and a higher percentage of carcasses than other local cattle. Molecular selection related to growth traits can be done by exploration of growth hormone genes in the population of Bali cattle. This study aims to detect the level of polymorphism of GH, GHR and Pit1 genes and their association with the body weight of Grati-Bali cattle as a first step to produce a MAS (marker assisted se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The previous research on several local Indonesian beef cattle, the A allele was also a common allele, such as on Grati-Bali Cattle 0.579 (Hartati, et al, 2021), Kebumen cattle 0.58 (Soewandi et al, 2021), Bali cattle 0.991 and Pesisir cattle 0.615 (Zulkharnaim et al, 2010). Likewise with other exotic cattle such as Simmental cattle, the most common genotype was the AA genotype (64.19%) and the A allele was the common alel (0.720) (Ardicli et al, 2017).…”
Section: Ghr|alui Gene Polymorphismmentioning
confidence: 89%
“…The previous research on several local Indonesian beef cattle, the A allele was also a common allele, such as on Grati-Bali Cattle 0.579 (Hartati, et al, 2021), Kebumen cattle 0.58 (Soewandi et al, 2021), Bali cattle 0.991 and Pesisir cattle 0.615 (Zulkharnaim et al, 2010). Likewise with other exotic cattle such as Simmental cattle, the most common genotype was the AA genotype (64.19%) and the A allele was the common alel (0.720) (Ardicli et al, 2017).…”
Section: Ghr|alui Gene Polymorphismmentioning
confidence: 89%
“…Genetic factors, such as single nucleotide polymorphisms in related genes, and non-genetic factors such as obesity, physical inactivity, smoking and alcohol consumption have been shown to play an important role in the development of tumours [1] [2]. Epidemiological studies have shown that digestive tract tumours have a high morbidity and mortality rate worldwide, especially in Asia [3]. According to relevant surveys, those who die from digestive tumours account for about 36.4% of all cancer deaths in China, much higher than the 5% in Europe and the United States [3].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that digestive tract tumours have a high morbidity and mortality rate worldwide, especially in Asia [3]. According to relevant surveys, those who die from digestive tumours account for about 36.4% of all cancer deaths in China, much higher than the 5% in Europe and the United States [3]. Pathophysiological studies have found that the occurrence of digestive tract tumours is related to biological processes such as cell proliferation, apoptosis, DNA damage repair, and also to a variety of genetic variants.…”
Section: Introductionmentioning
confidence: 99%